Job retention among older workers in central and Eastern Europe. Issue 2 (3rd July 2018) - Hardy, Wojciech; Kiełczewska, Aneta; Lewandowski, Piotr; Magda, Iga
ABSTRACT: We study job retention rates – the shares of workers who continue to work in the same job over the next five years – in Czechia, Hungary, Poland and Slovakia. Job retention among older workers is key to prolonging careers and increasing employment of older people which in turn is a crucial challenge for these countries. We find that the retention rates among workers aged 55–59 are low and amount to about a half of the retention rates among prime aged workers. Only in Poland the retention rates of older workers have increased for both men and women between 1998 and 2013. The individuals least likely to retain jobs after the age of 60 were women, those with lower education, working in industry, in medium or low-skilled occupations, and those living with a non-working partner. The policies aimed at encouraging job retention in Central and Eastern Europe should focus on these groups of workers.